Kindle Fire : Amazon's heated battle for the tablet market - Sawhney, Mohanbir S. (SAGE knowledge. Cases., 2016)
This case is intended to illustrate to readers the challenges faced in 2011-2013 by Amazon's CEO, Jeff Bezos, as he guided his company into the exploding tablet market. Faced with the tough decision between focusing on the e-reader market - which Amazon had come to dominate with its Kindle product line - and making a foray into tablets - for which it had no expertise - Bezos took the brave decision to chose the latter.